Valuable insights into general practice staff's experiences and perspectives on AI-assisted diabetic retinopathy screening—An interview study - Krogh, Malene; Hentze, Malene; Jensen, Morten Sig Ager; Jensen, Martin Bach; Nielsen, Marie Germund; Vorum, Henrik; Kolding Kristensen, Jette (Frontiers in Medicine, 2025)
AimThis study explores the hands-on experiences and perspectives of general practice staff regarding the feasibility of conducting artificial intelligence-assisted (AI-assisted) diabetic retinopathy screenings (DRS) in general practice settings.MethodThe screenings were tested in 12 general practices in the North Denmark Region and were conducted as part of daily care routines over 4 weeks. Subsequently, 21 staff members involved in the DRS were interviewed.ResultsThematic analysis generated four main themes: (1) Experiences with DRS in daily practice, (2) Effective DRS implementation in general practice in the future, (3) Trust and approval of AI-assisted DRS in general practice, and (4) Implications of DRS in general practice. The findings suggest that general practice staff recognise the potential for AI-assisted DRS to be integrated into their clinical workflows. However, they also emphasise the importance of addressing both practical and systemic factors to ensure successful implementation of DRS within the general practice setting.ConclusionFocusing on the practical experiences and perspectives of general practice staff, this study lays the groundwork for future research aimed at optimising the implementation of AI-assisted DRS in general practice settings, while recognising that the insights gained may also inform broader primary care contexts.